Barriers to early and effective overactive bladder management in male patients with lower urinary tract symptoms. - Paul Rasner; Maria Arcila-Ruiz; José Ailton Fernandes Silva; Umaphorn Nuanthaisong; Sung Yung Cho; Eric Chung (PLoS ONE)
Overactive bladder is underdiagnosed and undertreated in men as symptoms overlap with benign prostatic obstruction. This study identified barriers urologists encountered in effectively managing overactive bladder in men with lower urinary tract symptoms. 60 urologists recruited across Australia, Brazil, Colombia, Russia, South Korea and Thailand via convenience sampling participated in in-depth interviews. They were asked about their understanding and management of overactive bladder in men with lower urinary tract symptoms. Thematic analysis identified six themes: (1) overactive bladder diagnosis in men with lower urinary tract symptoms is complicated by the multi-factorial causes of storage symptoms; (2) patient-reported outcome tools are underutilized by urologists; (3) stigmatization and normalization of overactive bladder discourage men from seeking care; (4) challenges exist in tracking overactive bladder symptoms and in patient-urologist communication; (5) the underestimation of overactive bladder contributes to the non-urgency of its management; and (6) urologists may not fully appreciate the trade-offs between different overactive bladder treatments. Encouraging patient-reported outcome tool usage and differentiating the safety profiles of antimuscarinics and beta-3 agonists may facilitate timelier overactive bladder diagnosis and increase confidence in adding-on treatment.